Use of failure mode and effect analysis to reduce patient safety risks in purchasing prescription drugs from online pharmacies in China - Hu, Qinyuan; Hu, Haiyao; Hu, Ming; Zhang, Jun; Gou, Liangwen; Shi, Shuping; Zhou, Jingyi; Zhou, Naitong; Huang, Zhen (Frontiers in Medicine, 2022)
Background: Online pharmacies have gradually penetrated the market, but pose risks to patients’ health. Failure Mode and Effect Analysis (FMEA) is an effective and reliable method for reducing pharmacy and medication risks. The purpose of this study was to conduct a prospective risk analysis of the process of purchasing prescription drugs from online pharmacies in China to guarantee drug quality and patient safety. Methods: The FMEA was performed at Sichuan University, China. A multidisciplinary team was assembled comprising a leader, four regulators, four pharmacists, two experts, etc. The process was composed of eight subprocesses: searching for prescription drugs, submitting medication requirements, completing patient information forms, dispensing, delivering, etc. Brainstorming was used to identify and prioritize failure modes, propose corrective actions, and reduce risks. Risk priority numbers were the main criterion and were obtained by multiplying three scores: severity, occurrence and detectability, which were scored by the team The team proposed corrective actions for each selected failure mode. Results: A total of forty-one potential failure modes were identified, and the causes, effects, and corrective actions of the 30 top failure modes were analyzed. The highest risk value was assigned to “photocopies of paper prescriptions uploaded were reused by patients.” Three failure modes for the S value of 5 were: “drugs are eroded and polluted by moisture or insects in the process of transportation,” “the qualification information of the pharmacies were absent or fake,” and “pharmacists fail to check prescriptions in accordance with Prescription Administrative Regulation.” Of the top failure modes, 36.67% were from Step 5, delivering the drug. After taking corrective measures to control risks, the risks reduced by 69.26%. Conclusion: The results of this study proves that the FMEA is a valuable tool for identifying and prioritizing the risks inherent in online pharmacies. This study shows that there are many potential risks in the process of purchasing prescription drugs from online pharmacies, especially in the drug delivery stage. Enhanced training and the introduction of smart devices may minimize risks. Online pharmacies and Chinese regulators should consider these findings for risk mitigation and the improvement of regulations pertaining to online pharmacies.